Potential mechanisms of cadmium removal from aqueous solution by Canna indica derived biochar - Cui, Xiaoqiang; Fang, Siyu; Yao, Yiqiang; Li, Tingqiang; Ni, Qijun; Yang, Xiaoe; He, Zhenli (The Science of the total environment, 2016)
The objective of this study was to investigate the mechanisms of cadmium (Cd) sorption on biochars produced at different temperature (300–600°C) and their quantitative contribution. The sorption isotherms and kinetics of Cd2+ sorption on biochars were determined and fitted to different models. The Cd2+ sorption data could be well described by a simple Langmuir model, and the pseudo second order kinetic model best fitted the kinetic data. The maximum sorption capacity (Qm) obtained from the Langmuir model for CIB500 was 188.8mgg−1, which was greater than that of biochars produced at other temperature. Precipitation with minerals, ion exchange, complexation with surface oxygen-containing functional groups, and coordination with π electrons were the possible mechanisms of Cd2+ sorption on the biochars. The contribution of each mechanism varied with the pyrolysis temperature. With increasing pyrolysis temperature, the contribution of surface complexation and metal ion exchange decreased from 24.5% and 43.3% to 0.7% and 4.7%, while the contribution of precipitation and Cd2+-π interaction significantly increased from 29.7% and 2.5% to 89.5% and 5.1%, respectively. Overall, the precipitation with minerals and metal ion exchange dominated Cd2+ sorption on the biochars (accounted for 73.0–94.1%), and precipitation with minerals was the primary mechanism of Cd2+ sorption on the high-temperature biochars (≥500°C) (accounted for 86.1–89.5%). [Display omitted] •Sorption capacity of metal on biochars is affected by pyrolysis temperature.•Biochar derived from Canna indica at 500°C has a high sorption capacity for Cd2+.•Cd2+ sorption on the biochars fits a pseudo second order and Langmuir model.•Precipitation and ion exchange mechanisms dominated Cd2+ sorption on the biochars.